Public Investment in a Developing Country Facing Resource Depletion - Alter, Adrian (IMF Working Papers; Working Paper ;, 2015)
This paper analyzes the tradeoffs between savings, debt and public investment in the Republic of Congo, a developing country with looming oil exhaustibility concerns. Our results highlight the risks to fiscal and capital sustainability of oil exporting countries from large scaling-up in public investment and oil price volatility in view of a projected decline in the oil revenue to GDP ratio. However, structural reforms that improve the efficiency of public investment can allow for a relatively faster buildup of sustainable public capital and sustain higher non-oil growth without adversely affecting the debt ratio or savings. Moreover, we show that even if a government pursues prudent fiscal policy that preserves resource wealth and debt sustainability in the face of exhaustible and volatile resource revenues, low public investment quality in the form of a misallocation of resources can hinder attainment of sustainable public capital and positive non-oil growth.